Peningkatan Kemampuan Membaca Pemahaman Isi Cerita Anak melalui Penggunaan Metode Cooperative Integrated Reading and Composition (CIRC) pada Siswa Kelas V SD Negeri Serangan Tahun Pelajaran 2016/2017 - Fatimatu Zahrah Abdurahman (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Abstract:This research aims to improve understanding of the content of children's stories read fifth grade students through the integration of cooperative methods of reading and composition (CIRC)in the fifth grade students of SD state Serangan. This type of research is classroom action research (PTK). Classroom action research was conducted in two cycles. The data collection technique using the test method, observation and documentation. The results showed that the assessment of reading comprehension skills at prasiklus average value of 70.3 students with classical completeness 44%. In the first cycle the average value increased by 74.2 students with classical completeness 74%. In the second cycle the average value of the percentage of students reaching 85.6 with a classical 86%.